Selection of inbred lines to produce sweet coro hybrids high on Iysine: II Lines. - Vega, María Cristina (2016)
The Maize Mexican Institute "Dr. Mario E. Castro Gil" at Universidad Autónoma Agraria Antonio Narro has developed endogamic lines with a tendency to produce sweet corn hybrids whose germ plasrn ineludes both the sugary-2 and the opaque-2 genes responsible for Iysine and sugar contento Sixty-one single crosses were obtained from a partial diallel among twentytwo S5 lines (twenty of which were included in Experiment I. Testers); such single hybrids were evaluated using a randornized complete block design in two sites in Mexico during 1994. Agronornic performance of the hybrids produced through the partí al diaIlel was superior to the performance obtained from trial hybrids in Experiment I (line x tester), resulting in a greater precociousness, better plant quality, and longer ears. Overdorninance effects among the lines played an important role in the manifestation of such traits. Hybrids and test crosses showed a similar response on traits such as amount of marketabIe ears, ear quality, number of green flag leaves, and grain color. Based on the previously mentioned results, twenty single hybrids were selected which can be used for semicommercial purposes.